Awareness of Knowledge or Awareness of Processing? Implications for Sleep-Related Memory Consolidation - Yordanova, Juliana (Frontiers Research Foundation, 2009)
The present study assessed the effects of awareness at encoding on off-line learning during sleep. A new framework is suggested according to which two aspects of awareness are distinguished: awareness of task information, and awareness of task processing. The number reduction task (NRT) was employed because it has two levels of organization, an overt one based on explicit knowledge of task instructions, and a covert one based on hidden abstract regularities of task structure (implicit knowledge). Each level can be processed consciously (explicitly) or non-consciously (implicitly). Different performance parameters were defined to evaluate changes between two sessions for each of the four conditions of awareness arising from whether explicit or implicit task information was processed explicitly or implicitly. In two groups of subjects, the interval between the pre-sleep and post-sleep sessions was filled either with early-night sleep, rich in slow wave sleep (SWS), or late-night sleep, rich in rapid eye movement (REM) sleep. Results show that implicit processing of explicit information was improved in the post-sleep relative to the pre-sleep session only in the early-night group. Independently of sleep stage, changes between sessions occurred for explicit processing of implicit information only in those subjects who gained insight into the task regularity after sleep. It is concluded that SWS but not REM sleep specifically supports gains in computational skills for the processing of information that was accessible by consciousness before sleep.